Cavity-tree use and frequency of response to playback by the Tropical Screech-Owl in northwestern Argentina - Schaaf, Alejandro Alberto (2019)
The Tropical Screech-Owl (Megascops choliba) is a nocturnal raptor with a wide distribution across the Neotropics, which uses cavity trees as nesting and roosting sites. Our objectives were to address cavity use by the Tropical Screech-Owl in the piedmont forest of Argentina and to evaluate if logging affects the availability of suitable cavities for nesting and roosting and the frequency of response of the species to playback. The Tropical Screech-Owl used trees with DBH values > 46 cm of three tree species (69% Calycophyllum multiflorum, 15% Phyllostylon rhamnoides, and 8% Cedrela angustifolia), besides standing dead trees (8%). The density of suitable cavities was significantly lower in logged forests than in the control site. The frequency of response of the species to playback was significantly lower at one logged site. Our results can contribute to delineate sustainable forest management to ensure the conservation of this owl in logged forest.